A highly efficient and selective antitumor agent based on a glucoconjugated carbene platinum(ii) complex. Issue 22 (9th May 2019) - Annunziata, Alfonso; Cucciolito, Maria Elena; Esposito, Roberto; Imbimbo, Paola; Petruk, Ganna; Ferraro, Giarita; Pinto, Valerio; Tuzi, Angela; Monti, Daria Maria; Merlino, Antonello; Ruffo, Francesco
Abstract : A Pt(ii ) complex with a glucosylated carbene shows very high in vitro cytotoxicity and selectivity toward malignant cells. Abstract : New five-coordinate Pt(ii ) complexes containing a glycosylated carbene fragment were synthesized. A member of this class shows very high in vitro cytotoxicity and an exceptional selectivity toward malignant cells. The complex lacking the sugary portion fails in the recognition of cancer cells. The results support the use of glycosylation in the design of carbene Pt-based anticancer agents.